Penerapan Metode SBABS Dalam Mencegah Stunting Di Wilayah Kerja Puskesmas Air Bangis Kabupaten Pasaman Barat - Yuliza anggraini; Liza Andriani (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2020)
Sanitation is one of the SDGs sustainable development goals, even though the field shows slow progress. The National Strategy for Community Based Total Sanitation (STBM) Policy refers to an acceleration strategy that aims to pursue SDGs targets. The purpose of implementing this program is to realize hygienic and sanitary community behavior independently in order to improve the highest public health status. STMB is an approach taken by various countries in the context of changing rural behavior which is widely applied to end open defecation and this problem is health related. Stop Open Defecation (SBABS) is one of the pillars contained in STMB in preventing stunting. Stop Open Defecation is a community-based total sanitation program that promotes a clean and healthy lifestyle, prevents the spread of environmentally-based diseases, increases the ability of the community to change their behavior not to defecate openly. The purpose of this study was to determine the effectiveness of the SBABS method in preventing stunting in infants aged 24-59 months in the working area of ​​Air Bangis Health Center, West Pasaman Regency. Methods: the study used a retrospective cohort design. The SBABS group as program recipients with the Non SBABS group who did not receive the program. The SBABS area group is Jorong Silawai Tengah and the non-SBABS area group is Kampung Padang Utara. The results showed that the proportion of baduta stunting in the SBABS group was 15.3%, with a normal height of 91.3% and good nutritional status (92.7%). There is a relationship between the toddler's height in the SBABS group and NON SBABS with a p-value of 0.012 but there is no relationship between the nutritional status of children under five in the SBABS group and NON SBABS with a p-value of 0.374 Conclusion: The SBABS method is effective in reducing the incidence of stunting in children aged 24-59 months in the working area of ​​Air Bangis Health Center, West Pasaman Regency.